2021
DOI: 10.3390/en14248389
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Long-Term Transition from Coal-Reliant to Low-Emission Power Grid and District Heating Systems in Poland

Abstract: Energy systems require technological changes towards climate neutrality. In Poland, where the power system is dominated by outdated coal-fired power plants, efforts to minimize the environmental impact are associated with high costs. Therefore, optimal paths for the development of the energy sector should be sought in order to achieve ambitious long-term strategic goals, while minimizing the negative impact on the consumers’ home budget. A methodology and a model for the development of the electricity and heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The research revealed that nuclear energy and offshore wind power play a substantial role in achieving climate neutrality in electricity generation. The projected development paths ensure a significant reduction in greenhouse gases and industrial emissions [77].…”
Section: Discussionmentioning
confidence: 99%
“…The research revealed that nuclear energy and offshore wind power play a substantial role in achieving climate neutrality in electricity generation. The projected development paths ensure a significant reduction in greenhouse gases and industrial emissions [77].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all the investments needed to reach that balance by the end of the planning horizon are optimally distributed across the planning period, so that the total surplus is maximized. The MARKALbased framework was widely utilized to assess developmental directions and the velocity of technological transition mainly for the energy sector, also towards its decarbonization, in Canada [28,29], Switzerland [30], Malaysia [31], Russia [32], the UK [33][34][35][36], the USA [37,38], Austria [39], China [40][41][42][43], Portugal [44][45][46], Italy [47], Iran [48], Turkey [49], Kazakhstan [50], Ireland [51], Poland [52], Greece [53], and Bulgaria [39].…”
Section: Markal-an Overviewmentioning
confidence: 99%
“…Pająk et al (2020) reviewed geological and hydrogeological data to assess the potential of geothermal water resources to cover the heating needs in Poland. Jaskólski and Bućko (2021) modeled a long-term transition from coal-dependent systems to low-emissions alternatives, identifying geothermal energy as a potential means to achieve long-term decarbonization goals. Kinelski et al (2021) proposed the application of smart technologies to lower emissions from district heating, estimating a reduction of approximately 275 kt of CO 2 due to the proposed changes.…”
Section: Introductionmentioning
confidence: 99%